Pengembangan Media E-Comic Berbasis Contextual Teaching and Learning pada Materi Sistem Persamaan Linear Tiga Variabel Kelas X SMA - Rosidah; Yudhi Alfian; Nurwati Djam’an; Hisyam Ihsan (Issues in Mathematics Education (IMED), 2023)
This development research aims: (1) Develop e-comic media based on contextual teaching and learning on the material of a three-variable linear equation system. (2) Knowing the quality of e-comic media based on contextual teaching and learning on the material of a three-variable linear equation system developed in terms of aspects of validity, practicality, and effectiveness. The type of this research is R&D with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The results of this research are (1) Valid e-comic media based on the results of the media expert and the material expert. (2) Practical e-comic media based on the results of the observation sheet on the implementation of the media in learning obtained an average percentage of 96.42%, and the percentage of teacher and student response questionnaires to e-comic media obtained a percentage of 97.91% and 90.51%. (3) Effective e-comic media based on the student learning outcomes test obtained effective results (≥ 85%) with class completeness of 87.87%. E-comic media based on contextual teaching and learning developed with the ADDIE model are valid, practical, and effective for use in learning mathematics on the material of a three-variable linear equation system.